ANALYSIS OF REFERRAL PROCEDURES ACCORDING TO LAW NUMBER 1 YEAR 1974 CONCERNING MARRIAGE AND THE COMPILATION OF ISLAMIC LAW (Study at KUA Rajabasa) - Ansori; Marefa, Dina (Progressive Law Review, 2021)
Marriage is a means to form a household as a bond that is recognized by the community where they live as legal husband and wife. However, as time goes by, it is not uncommon to have quarrels between husband and wife caused by third parties, economics, and other things, resulting in divorce. Rujuk means returning to life as husband and wife between a man and a woman doing divorce by way of talak while still in iddah without marriage who has the right to reconcile her husband as a balance of her divorce rights. The purpose of the study is to understand the procedure for reconciliation according to Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law studies at the KUA Rajabasa, and to understand the comparative analysis of law related to the synchronization of procedures for reconciliation according to Law Number 1 of 1974 concerning marriage and the Compilation of Laws.